SMALL AND MEDIUM SCALE ENTERPRISES SUSTAINABILITY IN A DEPRESSING ECONOMY: THE STRATEGIC ROLE OF NIGERIAN ACCOUNTANTS - NWINEE, KPURUGBARA,; AKPOS, YIKAREBOGHA, EROROGHA; UCHE, AHIUZU, LEVI (IJRDO - Journal of Applied Management Science, 2017)
This paper focused on examining Small and Medium Scale Enterprises Sustainability in a Depressing Economy: The Strategic Role of Nigerian Accountants. This study took a descriptive survey approach and data was sourced from the 177 completed and returned five point likert scale questionnaire administered on accountants drawn from 40 SMEs in Rivers and Enugu State. T-test was used to analyze the data gathered with the aid of 20.0 version of statistical package for social sciences (SPSS). It was observed that SMEs in Nigeria are challenged by the poor national economic outlook that is hampering their competitiveness and threatening their sustainability. Hence, the study concludes that to satisfy the three bottom-line or pillars of sustainability, Nigerian accountants must be made strategic internal partners in SMEs as they have very important roles to play especially in the areas of environmental and economic sustainability of the firms. It was recommended that SMEs should engage in their employ qualified accountants who can guide and advice it on financial matters in other to enhance their sustainability, Training of accountants on environmental disclosure is very key to the sustainability of SMEs, There is need to ensure that SMEs do not just focus on immediate gains when developing their strategies, they should as a matter of strategic importance inculcate sustainability components in their strategies